The Greening of Economic Policy Reform Volume II: : Case Studies - World Bank. (Washington, D.C.: The World Bank, 1997)
This report, in two volumes, addresses environmental impacts stemming from economy-wide policy reforms, and seeks to clarify the nature of the economic, physical, institutional, and cultural aspects of their relationship. Volume 1 summarizes the case studies and synthesizes their key principles. Volume 2 explores the case studies in full length. They reflect a wide range of country situations and environmental problems. Pollution issues are addressed, such as air quality and energy use in Poland and Sri Lanka, while a variety of natural resource-related issues are covered in the other studies:deforestation and land degradation in Costa Rica; migration and deforestation in the Philippines; agricultural land degradation due to overgrazing in Tunisia, fertility losses due to extension of cultivation areas in Ghana; water resource depletion in Morocco; and wildlife management in Zimbabwe. The case studies also use a variety of analytical methods to illustrate the different approaches to identifying the environmental implications of economy-wide reforms. These methods range from tracing the links between economic incentives and resource use through direct observation, to relying on more complex economic modeling of policies and their environmental effects. In all the studies, however, the analytical approach uniformly requires identifying key environmental concerns and relating them to the agenda of priority sectoral and macroeconomic reforms.
Keywords: Ecology; Euthenics; Nature and nurture; Adaptation (Biology)